Migration and School: Perceptions of Primary School Teachers About Migrant Children - Muñoz-Labraña, Carlos (2021)
The research aimed to analyze the perceptions that primary school teachers have of migrant children. The study was conducted in four public schools in Concepción, Chile. An in-depth interview as a data collection technique was used and involved 20 teachers of both sexes who work in educational establishments that have received migrant children in the last two years. The results indicate that migrants have become a concern in the school and a phenomenon that is here to stay. It is a phenomenon that divides the teaching staff at times, and for which they consider themselves unprepared since migrant children make teaching work in the classroom more complex. They perceive migration as a process closer to other countries’ reality and difficult to understand, especially for the long-serving staff. However, the research shows that teachers positively value the increase in enrollment, as well as the possibility of talking about diversity in the classroom and thinking about the country and the continent’s reality. They also value the importance of language to communicate and due respect for teachers.